Supermarket contracts, income, and changing diets of farm households: Panel data evidence from Kenya - Dennis O. Ochieng (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
In many developing countries, supermarkets are increasingly replacing traditional markets as preferred points of food purchases in urban areas. This has welfare implications on smallholder farmers that supply supermarkets. While previous studies have analyzed the welfare effects of smallholder participation in supermarket channels, many have focused on economic effects alone. Very little is known about the effects on farm household diets. Besides, most existing studies that have looked at economic effects used cross-sectional data that are limited in controlling for time-invariant differences between supermarket and traditional channel farmers. This study uses panel data from vegetable farmers in Kenya to examine the effects of supermarket contracting on farm household income and diets. Supplying supermarkets has increased household income by 66%, and is associated with 8% higher consumption of calories, as well as better dietary diversity, and higher levels of zinc consumption. Using these results for simple simulations suggests that wider participation of smallholders in supermarket channels could reduce the prevalence of undernourishment by 8% and the prevalence of zinc deficiency by 12%. Hence, enhancing smallholder market access could significantly contribute to reduction of undernourishment and micronutrient malnutrition and increased income of farm households.
Keywords: O12; O13; Q12; Q13; Q18; 330; supermarkets; smallholder farmers; incomes; diets; Kenya